An updating on Cryptosporidium parvum in the water buffalo - G. Cringoli (Italian Journal of Animal Science, 2010)
A cross-sectional survey of Cryptosporidium parvum infection in the water buffalo was carried out in central Italy. The survey was carried out on a sample of 90 farms, selected using a grid approach within a Geographical Information System, followed by proportional allocation. On each farm, faecal samples were collected from three to five asymptomatic buffalo calves, aged from 1 to 9 weeks (total number = 347). Each sample was tested for the presence of copro-antigens of C. parvum using a commercially available ELISA. Out of the 90 farms, 22 (24.4%) resulted positive. With respect to animals, out of the 347 faecal samples, 51 (14.7%) were found to have antigens of C. parvum. The results of the logistic regression model showed a positive association between the positivity to C. parvum and the high number of buffaloes on farms.